2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8794342
|View full text |Cite
|
Sign up to set email alerts
|

Learning Quickly to Plan Quickly Using Modular Meta-Learning

Abstract: Multi-object manipulation problems in continuous state and action spaces can be solved by planners that search over sampled values for the continuous parameters of operators. The efficiency of these planners depends critically on the effectiveness of the samplers used, but effective sampling in turn depends on details of the robot, environment, and task. Our strategy is to learn functions called specializers that generate values for continuous operator parameters, given a state description and values for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…There is a body of related work on guiding the choice of continuous parameters given the abstract action sequences (Chitnis et al, 2019;Kim et al, 2018Kim et al, , 2019a. In particular, we directly build on our previous work on using GANs for learning a sampler (Kim et al, 2018(Kim et al, , 2019a, but in this work we use advanced GAN training technique that offers much more stable training (Gulrajani et al, 2017).…”
Section: Learning To Guide Planningmentioning
confidence: 99%
“…There is a body of related work on guiding the choice of continuous parameters given the abstract action sequences (Chitnis et al, 2019;Kim et al, 2018Kim et al, , 2019a. In particular, we directly build on our previous work on using GANs for learning a sampler (Kim et al, 2018(Kim et al, , 2019a, but in this work we use advanced GAN training technique that offers much more stable training (Gulrajani et al, 2017).…”
Section: Learning To Guide Planningmentioning
confidence: 99%
“…Learning techniques have been integrated into many aspects of TAMP systems, from learning samplers for continuous values [13], [14], [15], [16] to learning guidance for symbolic planning [9], [10], [14]. The latter is our focus in this paper; we assume samplers are given, and we aim to learn operators that enable symbolic planning in TAMP.…”
Section: B Learning For Task and Motion Planningmentioning
confidence: 99%
“…Moreover some studies have found that some types of modular structures emerged in standard neural networks [17,18]. New strategies have been proposed for combining the modularity of neural networks with meta learning [12,19,20], with a general trend of learning modules that can be recombined to solve new tasks, leading to better performance and combinatorial generalization.…”
Section: Related Workmentioning
confidence: 99%